The Agency Problem in the Merger of Vistula & Woĺczanka Ltd. and W. Kruk Ltd. - Błazėj Socha (Comparative Economic Research. Central and Eastern Europe, 2009)
The article discusses the behavior of company bodies and possible conflicts of interests occurring among them during company takeover. In this context, the insider management model, popular in Poland, is discussed. Its implications have been presented using the example of the merger between Vistula & Woĺczanka Ltd. and W. Kruk Ltd.
Keywords: 330